Epidemiological Study of Schistosomiasis among School Pupils in Kurfi LGA, Katsina State, Nigeria - Abbas Usman; Nkiru Charity Eberemu; Orpin, J. B. (UMYU Journal of Microbiology Research)
Study’s Excerpt: • Schistosomiasis remains prevalent among pupils in Kurfi LGA due to unsafe freshwater exposure. • Schistosoma haematobium infection was more common than S. intercalatum among the study group. • Pupils at schools near water bodies showed higher infection rates, especially in Amadi Kurfi school. • No significant link was found between infection and gender or age, but education level was a factor. • The area is endemic for S. haematobium; improved hygiene and molecular diagnostics are suggested. Full Abstract: Schistosomiasis is a disease of poverty that leads to chronic ill-health. Infection is acquired when people come into contact with fresh water infested with the larval forms (cercariae) of parasitic blood flukes, known as schistosomes. The study was conducted to determine the prevalence of Schistosoma haematobium and Schistosoma intercalatum among primary school pupils in Kurfi Local Government Area of Katsina State, Nigeria. Questionnaires were administered to 300 randomly selected pupils to assess the socio-demographical information, risk factors, and human water contact behavior. Sedimentation techniques were used to determine the prevalence, while the Medi-Test Combi-9 test strip was used for chemical examinations. Out of 49 samples collected, 300 are positive for hematuria while 26 are positive for proteinuria and, 59 are positive for S. haematobium and only 6 are positive for S. intercalatum, and in comparison, the prevalence is significantly higher in Amadi Kurfi Qur’anic Primary School with 29 (54%) of S. haematobium and 4 (66.7%) of S. intercalatum, which could be due to the closeness of the school to the water body when compared to other schools. The infections are not influenced by gender and age group (OD = 1.00 and 1.53) and (P = 7.03 and <0.01), respectively, but pupils whose parents have no formal education have (OR) 38.9 higher times of infections than those that have no formal education (P = 0.02). Conclusively, the study area is endemic with S. haematobium and further molecular identification of S. intercalatum is recommended in addition to personal hygiene.